Beyond Linguistic Failure: Disfluency as a Cognitive Coordination Strategy in International Diplomatic Oratory - Farah Aulia Dewi; Dewi Kustanti; Cipto Wardoyo (GLENS: Global English Insights Journal, 2026)
Diplomatic speeches play a vital role in international relations, where precise language is essential to maintain national authority and avoid misinterpretation. Despite this expectation, speech disfluencies frequently occur even in high-stakes formal contexts. While previous studies have primarily examined disfluency in informal or media settings, its strategic role in diplomatic oratory remains underexplored. This study investigates the types, causes, and functions of speech disfluency in a keynote speech delivered by Indonesia’s Foreign Minister. Using a qualitative descriptive approach, this study analyzes a 30-minute speech consisting of 118 utterances, in which 72 instances of disfluency were identified. The data were transcribed and analyzed through classification based on Clark and Clark’s (1977) framework, followed by frequency analysis to determine dominant patterns. The findings show that filled pauses (33.33%) and silent pauses (29.17%) are the most prevalent types. These disfluencies function not merely as speech disruptions but as adaptive cognitive strategies that support lexical retrieval, manage cognitive load, and maintain speech continuity in a second language context. The study concludes that disfluency in diplomatic speech should be understood as a functional component of real-time language production, particularly in high-pressure communicative environments.